Decreases in State and Trait Anxiety Post-psilocybin: A Naturalistic, Observational Study Among Retreat Attendees - Kiraga, Maggie Kamila; Kuypers, Kim P. C.; Uthaug, Malin Vedoy; Ramaekers, Johannes G.; Mason, Natasha Leigh (Frontiers in Psychiatry, 2022)
Anxiety disorders are the most common type of psychiatric disorders among Western countries. Evidence-based treatment modalities including pharmacological and cognitive-behavioral therapy result in deficient treatment responses. Historical and recent research suggests psychedelic drugs may be efficacious in alleviating anxiety-related symptoms among healthy and clinical populations. The main aim of the present study was investigation of the effects of psilocybin-containing truffles, when taken in a supportive group setting, on ratings of state and trait anxiety across self-reported healthy volunteers. Attendees of psilocybin ceremonies completed a test battery before the ceremony (baseline), the morning after, and one week after the ceremony. The battery included questionnaires assessing state and trait anxiety (State-Trait Anxiety Inventory), mindfulness capacities (Five Facet Mindfulness Questionnaire), and personality (Big Five Inventory). Additionally, the psychedelic experience was quantified with the Persisting Effects Questionnaire and the Ego Dissolution Inventory. Fifty-two attendees (males= 25; females= 25; others= 2) completed the baseline assessment, 46 (males= 21; females= 24; others= 1) completed assessments the morning after the ceremony, and 23 (males= 10; females= 13) completed assessments at the one-week follow-up. Average psilocin consumption across individuals was 27.1 mg. The morning after the ceremony, we observed medium reductions in anxiety measures (both state and trait) compared to baseline (d= 6.4; p< 0.001 and d= 6; p= 0.014, respectively), which persisted over a one-week period post-ceremony (d= 6.7; p= 0.001 and d= 8.6; p= 0.004, respectively). One week post-ceremony, the non-judging facet of the mindfulness scale increased (d= 1.5; p= 0.03), while the personality trait neuroticism decreased (d= 5.2; p= 0.005), when compared to baseline. Ratings of ego dissolution (mean: 59.7, SD: 28.3) and changes in neuroticism, were the strongest predictors of reductions in state and trait anxiety, respectively. Results suggest rapid and persisting (up to one week) anxiolytic effects in individuals with sub-clinical anxiety symptoms, which are related to acute ego dissolution, as well as lasting changes in trait neuroticism. Results also add support to the feasibility and potential efficacy of group sessions with psychedelics. To understand whether these effects extend to populations suffering from heightened anxiety, and the mechanisms involved, further research is needed.